Sex differences in abnormal gluten response and predictors of gluten sensitivity in patients with schizophrenia - Dzikowski, Michał; Rog, Joanna; Juchnowicz, Dariusz; Rymuszka, Anna; Karakula-Juchnowicz, Hanna (Frontiers in Immunology, 2025)
IntroductionImmune-inflammatory dysregulations are linked to shifts in specific gut microbiota genera, underscoring the importance of the gut–brain connection in schizophrenia (SZ). However, the immune-inflammatory aspects of sex differences in SZ remain largely unexplored. The aims of this study were (1) to identify sex-related differences in inflammatory response, intestinal biomarkers, and gluten sensitivity in SZ and (2) to determine potential factors underlying variability in the immune response to gluten in this population.MethodsA total of 102 individuals with SZ and 60 healthy controls (HC) were included in the study.ResultsElevated titers of anti-gliadin (AGA) IgA were found in 26% of individuals with SZ compared to 22% of HC and elevated AGA IgG in 30% of SZ patients compared to 20% of HC. The IgG levels were higher in men than in women, regardless of health status. Significant differences in the levels of AGA IgG and deamidated gliadin (dGP) IgG were observed between men and women with SZ, with higher concentrations detected in men. Factors differentiating patients with positive AGA IgA antibodies included tissue transglutaminase (tTG) IgA levels, high-sensitivity C-reactive protein (hs-CRP) levels, and age. Factors associated with positive AGA IgG antibodies included dGP and anti-Saccharomyces cerevisiae (ASCA) antibody levels, negative symptoms of SZ, and age of onset.DiscussionThis is the first study to examine sex-related differences and illness stage in the immune response to gluten among SZ patients. Stronger inflammatory responses were found in men, suggesting sex-related disparities in gluten-related immune activation. These findings highlight a complex interplay between hormones, immune function, intestinal barrier integrity, and psychiatric symptoms. Further longitudinal research is needed to clarify these mechanisms and their clinical significance.